The long-term high-temperature history of the central Namaqua Metamorphic Complex: evidence for a mesoproterozoic continental back-arc in southern Africa - Bial, Julia; Büttner, Steffen H.; Schenk, Volker; Appel, Peter (Precambrian research, 2015)
Reaction textures, equilibrium assemblage modelling and in situ U-Th-total Pb monazite and zircon U-Pb LA-ICP-MS dating of metapelitic rocks provide new insights to the tectono-metamorphic evolution of the Kakamas Terrane in the central Namaqua Metamorphic Complex (NMC). Staurolite inclusions in garnet porphyroblasts and patchy sillimanite intergrowths probably after kyanite record an amphibolite facies prograde stage of the Mesoproterozoic Kibran/Namaquan orogeny. The peak assemblages in metapelites are (i) osumilite, replaced by alkali feldspar+cordierite+orthopyroxene+quartz±plagioclase, (ii) spinel+quartz and (iii) corundum+quartz in the southwest of the study area and (iv) garnet+cordierite+quartz+sillimanite±alkali feldspar±plagioclase±biotite parageneses in the northeast. The spinel+quartz bearing metapelites in the highest-grade domains in the southwest of the study area equilibrated at 800-900°C at ∼5.0kbar. Osumilite may have formed at somewhat higher temperatures in excess of 900°C. In shallower crustal levels, exposed in the northeast of the study area, the metamorphism reached 640-680°C at 4.0-4.5kbar, followed by minor decompression to 3.5kbar. Isobaric cooling during retrogression in the highest-grade rocks forms biotite+sillimanite+quartz intergrowths replacing Fe-Mg peak and post-peak phases at 650-700°C. Minor re-heating overprints these textures forming a new garnet generation. P-T conditions lower than the middle/upper amphibolite facies conditions are not recorded in the study area. Two generations of zircon showing oscillatoric zonation document an early Kibaran stage of anatexis in metapelites at 1351-1299Ma, followed by a more commonly seen younger stage of partial melting at ∼1200Ma. The UHT peak metamorphism is either associated with the first anatexis at ≥1300Ma or, more likely, is an early stage of the widespread partial melting in the NMC at ∼1200Ma. The monazite data set shows, in addition to ∼1200Ma ages, two further age populations. The first of these, dated as 1090±9-1071±6Ma, is associated with the second garnet growth. Younger monazite rims, formed at ∼1000Ma in lower grade rocks, are not related to other mineral reactions or textures and are interpreted as forming in relation to late-orogenic fluid influx. The long-lasting high-temperature history (>650°C) between ∼1350 and <1100Ma, locally reaching UHT-conditions, with slow cooling and heating episodes at near-constant mid-crustal pressures is not well compatible with crustal thickening and continent-collision models that have been proposed in the existing literature. We interpret the Mesoproterozoic evolution of the high-temperature crust in the central NMC as related to long-lasting, steady heat transfer from the mantle into a thinned lithosphere in a continental back-arc mobile belt setting, reaching higher granulite facies and in places UHT conditions during the Mesoproterozoic Kibaran/Namaquan orogeny.